LOGICAL MEANING REALIZATIONS IN THE AGREEMENT TEXT ON COMMON EFFECTIVE PREFERENTIAL TARIFF SCHEME FOR THE ASEAN FREE TRADE AREA - Sunardi Sunardi (Proceedings Education and Language International Conference, 2017)
This study aims at describing the lexicogrammatical realizations of logical meaning in the agreement text on common effective preferential tariff (CEPT) scheme for the Asean free trade area. The text under study was taken from http://asean.org/asean-economic-community/asean-free-trade-area-afta-council/agreements-declarations/. The logical meaning in this study refers to the grammatical and semantic unit formed when two or more clauses are linked together in certain systematic and meaningful ways under the theoretical framework of clause complex in systemic functional linguistics (SFL). The text was analyzed by identifying the boundaries of all clause complexes that made the text. The analysis emphasized on finding the types and the meanings of logical connection between clauses in the clause complexes. The findings show that the sentences in the agreement text under study use clause complexes (54%) more than clause simplexes (46%), showing the complexity of its sentence structure. This complexity is also supported by the fact that most of the clause simplexes use embedded clauses (63%) to give more meanings into the clause simplexes. In terms of interdependency relationship between clauses in clause complexes, the text uses significantly more hypotaxis (81%) than parataxis (19%). Keywords: Asean free trade area, common effective preferential tariff (CEPT) scheme, logical meaning, clause complex, hypotaxis, parataxis